Effects Of Organizational Culture And Perceived Organizational Support On Organizational Citizenship Behavior With Organizational Commitment As Mediator At PT Kimia Farma - Romma Rio Putra; Riyanto, Setyo (Publikasi Indonesia, 2025)
Abstrak. This study aims to analyze the influence of OC and POS on OCB with OCM as a mediating variable at PT Kimia Farma Tbk. Data collection was conducted using simple random sampling through a cross-sectional online survey with a self-administered questionnaire approach, involving 187 employees from the Kimia Farma Veteran unit. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study indicate that OC, POS, and OCM have a positive and significant influence on OCB. Additionally, OCM was found to play a significant mediating role in the relationship between OC and OCB, as well as between POS and OCB. These findings emphasize the importance of organizational commitment in strengthening the influence of organizational culture and perceptions of support on the enhancement of OCB.